Unexpected Beneficial Effect of ortho-Substituents on the (S)-Proline-Catalyzed Asymmetric Aldol Reaction of Acetone with Aromatic Aldehydes - Martínez, Alberto; van Gemmeren, Manuel; List, Benjamin (Synlett, 2014)
An intriguing effect of electronegative 2,6-substituents on the stereochemical outcome of (S)-proline-catalyzed aldol reactions between benzaldehyde derivatives and acetone is reported. Remarkably high enantioselectivities can be achieved with such substrates.
Keywords: aldehyde; aldol reaction; asymmetric catalysis; organocatalysis; proline